3D MXene‐Based Flexible Network for High‐Performance Pressure Sensor with a Wide Temperature Range. Issue 6 (25th December 2022) - Xie, Yimei; Cheng, Yongfa; Ma, Yanan; Wang, Jian; Zou, Junjie; Wu, Han; Yue, Yang; Li, Baowen; Gao, Yihua; Zhang, Xin; Nan, Ce‐Wen
Abstract: With the increasing popularity of smart wearable devices, flexible pressure sensors are highly desired in various complex application scenarios. A great challenge for existing flexible pressure sensors is to maintain high sensitivity over a wide temperature range, which is critical for their applications in harsh environments. Herein, a flexible piezoresistive sensor made of polyetherimide (PEI) fibrous network evenly covered with MXene nanosheets is reported to construct conductive pathways, showing ultrahigh sensitivity over a wide temperature range from −5 °C (sensitivity of 80 kPa −1 ) to 150 °C (20 kPa −1 ), low detection limit of 9 Pa, fast response time of 163 ms, outstanding durability over 10 000 cycles at room temperature, 2000 cycles at 100 °C and 500 cycles at −5 °C. The pressure sensor can monitor various human activities in real‐time, apply to human–machine interaction, and measure pressure distribution. It also can sensitively respond to external mechanical stimuli at 150 °C and extremely low temperature (in liquid nitrogen). Moreover, the fibrous network exhibits an excellent Joule heating performance, which can reach 78 °C at an applied voltage of 12 V. Thus, the piezoresistive sensor has considerable potential for wearable garments and personal heating applications in harsh temperature conditions. Abstract : A highly‐sensitive piezoresistive sensor based on 3D MXene/polyetherimide network is proposed. The sensor exhibits ultrahigh sensitivity in a wide temperature range from 80 kPa −1 at −5 °C to 20 kPa −1 at 150 ° C, low detection limit of 9 Pa, outstanding durability over 10 000 cycles at room temperature, 2000 cycles at 100 ° C and 500 cycles at −5 ° C.